PENGARUH TERAPI BEKAM TERHADAP SKALA NYERI SENDI PADA LANSIA DENGAN ARTRITIS REUMATOID DI DESA PARSANG KECAMATAN KOTA SUMENEP - Syaifurrahman Hidayat; Misbahol Arifin (Fakultas Ilmu Kesehatan, 2016)
Artritis reumatoid constitute cutoimmune disease (disease that happen when the body attacking by it’s own immune system), Resulting inflamation in long time on linge.Purposes this research to knowing inflvence copping therapy agamt all tinge pain with artritis reumatoid in village purpasange city districh sumenep. Pre experimental research design in one group (one groub pre-test post- test). Population in this research is so respondents, sampling technigues using simple rondow sampling to obtain a sample of 45 respondents. Analysis of the test resvlts wilcoxon signed rank test obtained with p:0,000 <a = 0,05 the meaming is there the effect copping therapy agamt all tinge pain with artritis reumatoid in village purpasange city districh sumenep. The result showed the pain scale before intervention experiencing moderate pain as many as 20 elderlys (44,4%), and that are experiencing pain as many as 25 elderlys (55.6%), when it was intervention elderly that have not pain 2 elderly (4,4%), mild pain as many as 26 ederlys (57,8%), There is the influence of cupping therapy on a scale of pain in older adults with rheumatoid arthritis in the village parsanga city districts Sumenep, From the result of this research expected to increase knowtedge and countermeansures of pain to create a positive habit avoiding achange of air can cause a pain.